Alveolar Breath Sampling and Analysis to Assess rihalomethane Exposures during Competitive Swimming Training - Lindstrom, A. B.; Pleil, J. D.; Berkoff, D. C. (Environmental Health Perspectives, 1997)
lveolar breath sampling was used to assess trihalomethane (THM) exposures encountered by collegiate swimmers during a typical 2-hr training period in an indoor natatorium. The breath samples were collected at regular intervals before, during, and for 3 hr after a moderately intense training workout. Integrated and grab whole-air samples were collected during the training period to help determine inhalation exposures, and pool water samples were collected to help assess dermal exposures. Resulting breath samples collected during the workout demonstrated a rapid uptake of two THMs (chloroform and bromodichloromethane), with chloroform concentrations exceeding the natatorium air levels within 8 min after the exposure began. Chloroform levels continued to rise steeply until they were more than two times the indoor levels, providing evidence that the dermal route of exposure was relatively rapid and ultimately more important than the inhalation route in this training scenario. Chloroform elimination after the exposure period was fitted to a three compartment model that allowed estimation of compartmental half-lives, resulting minimum bloodborne dose, and an approximation of the duration of elevated body burdens. We estimated the dermal exposure route to account for 80% of the blood chloroform concentration and the transdermal diffusion efficiency from the water to the blood to in excess of 2%. Bromodichloromethane elimination was fitted to a two compartment model, which provided evidence of a small, but measurable, body burden of this THM resulting from vigorous swim training. These results suggest that trihalomethane exposures for competitive swimmers under prolonged, high-effort training are common and possibly higher than was previously thought and that the dermal exposure route is dominant. The exposures and potential risks associated with this common recreational activity should be more thoroughly investigated.